Challenges in health-care service use among Burmese refugees: A grounded theory approach. (9th August 2019) - Yalim, Asli Cennet; Kim, Wooksoo; Kim, Isok
ABSTRACT: The timely use of health-care services is essential to achieve the best health outcomes. We explore barriers to health-care access among refugees from Burma through interviews with key community informants who serve their community as interpreters, health-care professionals, paraprofessionals, and/or representatives. The interviews with a convenience sampling of 11 leaders from Burmese and Karen ethnic communities revealed three stages of health-care use (i.e., before, during, and after doctor's appointments), in which their community members encounter difficulties in accessing health-care services. Using grounded theory analysis approach, specific difficulties and cultural considerations for each stage were emerged. This study suggests that training programs for health-care providers on refugee populations' needs, cultural expectations, attitudes, and health behaviors may ease the process for refugees during each of these three stages. Interpreters as cultural brokers have an important role in facilitating cross-cultural communications not only before and during the appointment but also after doctor's visits, such as in the pharmacy and labs.